Patrimonio cultural para la diversificación de la oferta turística del cantón Portoviejo. - Vásquez vera, Wagner Roberto (2015)
The research proposal was aimed at designing a cultural heritage tourism product Portoviejo Canton. To develop the methodological procedure the process of developing tourism products according to authors, which was organized into phases, stages and methods that were applied in the research study, a tourist diagnosis of the canton involved was developed was used, which is could identify cultural attractions, which were potentiated for inclusion into the product. 10 potentiated cultural heritage the same as were used for the preparation of 4 tours, the segment that targets the product is the key market and proposed according to the PYMTE potential were selected and aims to meet the demand of tourists both domestic and foreign, thus giving a quality service in guided tours. Was selected as the name of the tourist product "are cultural heritage" because Portoviejo has potential cultural heritage, and to pretend this proposal promote socio economic development of the communities involved in tourism, preserving cultural heritage, historical offering giving tourists a new product option to your hands, increasing the number of tourists in order to diversify tourism in the canton Portoviejo, and the development of tourism in the province and the region.